2015
DOI: 10.1074/jbc.m114.622415
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic Antidepressant Amitriptyline-induced Glial Cell Line-derived Neurotrophic Factor Production Involves Pertussis Toxin-sensitive Gαi/o Activation in Astroglial Cells

Abstract: Background: A significant non-neural, monoamine-independent mechanism underlies the antidepressant effect of amitriptyline. Results: Amitriptyline-evoked GDNF production is mediated by pertussis toxin (PTX)-sensitive G␣ i/o . Conclusion: PTX-sensitive G␣ i/o activation is critical for the cascade that underpins the biological effect of amitriptyline. Significance: Further elaboration of the intracellular mechanism of amitriptyline could lead to greater understanding of depression and novel antidepressant treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 62 publications
(91 reference statements)
4
33
0
Order By: Relevance
“…One of these drugs could be the tricyclic antidepressant amitriptyline, as it was shown to decrease the release of BDNF [91], and, at the same time, increase that of GDNF at least in glia [92]. If one considers the picture emerged from a more precise dissection of the nociceptive circuitries in the substantia gelatinosa of the spinal cord (Figure2), amitriptyline has the potential to target at the same time a pro-(BDNF) and an antinociceptive (GDNF) factor at this very important relay station.…”
Section: An Interesting Option For Developing New Drugs Is Thus Targementioning
confidence: 99%
“…One of these drugs could be the tricyclic antidepressant amitriptyline, as it was shown to decrease the release of BDNF [91], and, at the same time, increase that of GDNF at least in glia [92]. If one considers the picture emerged from a more precise dissection of the nociceptive circuitries in the substantia gelatinosa of the spinal cord (Figure2), amitriptyline has the potential to target at the same time a pro-(BDNF) and an antinociceptive (GDNF) factor at this very important relay station.…”
Section: An Interesting Option For Developing New Drugs Is Thus Targementioning
confidence: 99%
“…12) Thus, although these findings demonstrate that the Gi/o protein is a key molecule regulating GDNF expression, it is not known whether direct activation of Gi/o protein could induce GDNF expression, and what mechanism might be involved after Gi/o protein activation.…”
Section: )mentioning
confidence: 80%
“…The concentrations of inhibitors (PTX, U0126, SU5402, and PD173074) used in this study selectively inhibit its target, and no other kinases, in rat primary cultured astrocytes. 12,19) U0126, SU5402, and PD173074 were dissolved in dimethyl sulfoxide (DMSO). The final concentration of DMSO was adjusted to 0.1% for drug treatment experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Distinct classes of antidepressants, such as tricyclic, tetracyclic antidepressants, and selective 5‐HT reuptake inhibitor (SSRI), increase GDNF production in rat C6 glial cells (C6 cells) and primary cultured rat astrocytes (primary astrocytes), but not in primary neurons . In addition, the antidepressant amitriptyline increased GDNF production via Gα i/o ‐coupled lysophosphatidic acid receptor 1 (LPAR1)/matrix metalloproteinase‐9 (MMP‐9)/fibroblast growth factor (FGFR)/ERK cascade . However, the precise intracellular signaling pathway between LPAR1/Gα i/o and MMP‐9 is yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition, the antidepressant amitriptyline increased GDNF production via Gα i/o -coupled lysophosphatidic acid receptor 1 (LPAR1)/matrix metalloproteinase-9 (MMP-9)/fibroblast growth factor (FGFR)/ERK cascade. 7,[9][10][11][12] However, the precise intracellular signaling pathway between LPAR1/Gα i/o and MMP-9 is yet unknown. It has been reported that G proteins regulate MMPs via intracellular signaling molecules, such as Src family tyrosine kinase, calcium (Ca 2+ ) ions, and protein kinase C (PKC).…”
Section: Introductionmentioning
confidence: 99%